Relationship between nursing stress and forgotten nursing care in the COVID-19 pandemic - Mohammad Farzanehfar; Sajjad Amiri Bonyad; Vahid Yousofvand; Arezou Karampourian; Salman Khazaei (Shahrekord University of Medical Sciences, 2023)
Background and aims: Long-term stress can lead to forgetfulness of nursing care and reduce the quality of nursing care. Therefore, this study aimed to determine the relationship between nursing stresses and missed nursing care during the COVID-19 pandemic. Methods: The present study was a cross-sectional study. This study included 268 nurses from various hospitals in 2022. Sampling was done by stratified quota method. Kalish and Williams' Forgotten Nursing Care and French's nursing stress questionnaires were used to collect data. Data were analyzed using Stata 14 at a significance level of 0.05. Results: The study showed a significant relationship between the expression of nursing stress and forgotten nursing care (P≤0.001). Average stress scores for nursing care and forgotten nursing care were obtained as 137.90±36.70 and 32.71±8.72, respectively. Conclusion: Most nurses reported much stress. Considering the positive correlation between nursing stress and forgotten nursing care, nursing managers are suggested to reduce missed nursing care with stress reduction workshops.